Docking Molecular Study, Pharmacokinetics Profile and Toxicity Prediction of Basil Plant (Ocimum basillicum) Compounds as Isocitrates Dehydrogenase Inhibitor - Imani, Fitril; Yusnita Rifai,; Herlina Rante,; Ansari Masri,; Andri Anugrah Pratama,; Musabbiha, (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2023)
This study aims to predict the compounds from Ocimum basillicum that have potential as glioma inhibitors by inhibiting the enzyme isocitrate dehydrogenase (IDH). Forty-two compounds from Ocimum basillicum were carried out by molecular docking to the IDH receptor using the AutodockTools 1.5.7 program and continued prediction of pharmacokinetic profile and toxicity using ADMETab 2.0 and Toxtree. The validation of the molecular docking method showed an RMSD value of 1.8509 A. As a result of the research, we discovered several compounds had the best interactions in our investigation. Those compounds were Apigenin, Catechin, Chloronergic Acid, Ellagic Acid, Quercetin, Rutin, Eriodictyol, and Chicoric Acid, with binding affinity values of -7.1, -6.7, -7.1, -7.1, -7.1, -8.5, -7.2, and -6.5, respectively. Several compounds are predicted to have the potential to be developed as glioma inhibitors. Furthermore, the ADMET's predictions show that these potential compounds still require improvement in pharmacokinetics and toxicity. However, further laboratory investigations like in vitro and in vivo assays need to be conducted.